Exome sequencing in 57 patients with self-limited focal epilepsies of childhood with typical or atypical presentations suggests novel candidate genes. (July 2020) - Rudolf, Gabrielle; de Bellescize, Julitta; de Saint Martin, Anne; Arzimanoglou, Alexis; Valenti Hirsch, Maria Paola; Labalme, Audrey; Boulay, Clotilde; Simonet, Thomas; Boland, Anne; Deleuze, Jean François; Nitschké, Patrick; Ollivier, Emmanuelle; et al.
Abstract: Objective: Self-limited focal epilepsies of childhood (SFEC) are amongst the best defined and most frequent epilepsy syndromes affecting children with usually normal developmental milestones. They include core syndromes such as Rolandic epilepsy or " Benign" epilepsy with Centro-Temporal Spikes and the benign occipital epilepsies, the early onset Panayiotopoulos syndrome and the late-onset Gastaut type. Atypical forms exist for all of them. Atypical Rolandic epilepsies are conceptualized as belonging to a continuum reaching from the "benign" RE to the severe end of the Landau-Kleffner (LKS) and Continuous Spike-Waves during Sleep syndromes (CSWS). GRIN2A has been shown to cause the epilepsy-aphasia continuum that includes some patients with atypical Rolandic epilepsy with frequent speech disorders, LKS and CSWS. In the present study, we searched novel genes causing SFEC with typical or atypical presentations. Methods: Exome sequencing was performed in 57 trios. Patients presented with typical or atypical SFEC, negative for GRIN2A pathogenic variant. Results: We found rare candidate variants in 20 patients. Thirteen had occurred de novo and were mostly associated to atypical Rolandic Epilepsy. Two of them could be considered as disease related: a null variant in GRIN2B and a missense variant in CAMK2A . Others were considered good candidates, including a substitution affecting a splice site in CACNG2 and missense variants in genes encoding enzymes involved in chromatin remodeling. Significance: Our results further illustrate the fact that atypical SFEC are more likely to have Mendelian inheritance than typical SFEC. Highlights: Exome sequencing was performed in 57 trios with typical or atypical Self-limited focal epilepsies of childhood (SFEC). Thirteen rare variants had occurred de novo . Two were considered as disease-causing: in GRIN2B and in CAMK2A. Others were considered good candidates, including a substitution affecting a splice site in CACNG2 and missense variants in genes involved in chromatin remodeling.